Elections and voters - Eijk, Cees Van Der (England, 2009)
This major new text by two leading authorities in the field provides a state-of-the-art assessment of what we know about voting behaviour and the character, consequences and significance of elections in democratic states. It shows how patterns of electoral behaviour have evolved over time and vary in different countries.
Keywords: Elections